Multivariate analysis on students' cognitive assessment, attitude, and skill evaluation in problem-based learning - Santoso, Sabar; Pramesti, Getut (Mathematics Education Journal, 2024)
To improve the quality of education, the Ministry of Education and Culture of the Republic of Indonesia designed the "Merdeka" curriculum. With this curriculum, there are three learning outcomes, namely cognitive (knowledge), affective (character or attitude), and psychomotor (skills) domains. The learning that can be applied to the "MERDEKA" curriculum is the problem-based learning model. The significance of a variable in the learning process is very important to research to evaluate the learning process, especially in problem-based learning. Thus, the research objective of this study is to provide evidence of the significance of students’ cognitive assessment, attitude, and skill evaluation in mathematics learning. This study is a quantitative research using two-way multivariable analysis of variance (MANOVA), to determine the significance of cognitive assessment (assessment of learning outcomes), character or attitude, and skills evaluation in three classes of VIII students using problem-based learning (PBL). A two-way MANOVA analysis was carried out with students' class and gender factors, using measurement variables: cognitive assessment, attitude, and skill evaluation. From the results of the analysis, it was found that problem-based learning can be applied to Mathematics classes because, with this learning, both male and female students, the student's cognitive assessment is equally good in the significance level 5%. The differences in attitude and skill evaluation occurred because of the uniqueness of male and female students.